2012
DOI: 10.1109/tpwrd.2012.2187344
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern-Recognition Approach for Detecting Power Islands Using Transient Signals—Part II: Performance Evaluation

Abstract: Part I of this paper describes the design and implementation of an islanding detection method based on transient signals. The proposed method utilizes discrete wavelet transform to extract features from transient current and voltage signals. A decision-tree classifier uses the energy content in the wavelet coefficients to distinguish islanding events from other transient generating events. The verification tests performed in Part I, for a two generator test system having a synchronous generator and a wind farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…Results reveal that over/under voltage relays take more than 600 ms while over/under frequency relays taking nearly 1 s to detect power islanding. It is concluded in [20] that both these relays present a larger non-detection zones as well. Fig.…”
Section: Microgrid Behavior At Islandingmentioning
confidence: 95%
See 3 more Smart Citations
“…Results reveal that over/under voltage relays take more than 600 ms while over/under frequency relays taking nearly 1 s to detect power islanding. It is concluded in [20] that both these relays present a larger non-detection zones as well. Fig.…”
Section: Microgrid Behavior At Islandingmentioning
confidence: 95%
“…4 Microgrid control changes involved upon disconnecting from the grid From Table 2 it shows that voltage vector shift relay takes less than 30 ms to detect power islanding. However, in [20] it has shown that voltage vector shift relays' reliability is less at lower settings and presents a higher non-detection zone at higher relay settings. Rate of change of frequency relay response times, which indicates to be above 150 ms, highly depends on the relay setting and power imbalance.…”
Section: Microgrid Behavior At Islandingmentioning
confidence: 99%
See 2 more Smart Citations
“…The disturbances inserted in the distribution system may cause power quality deterioration. The passive method uses wavelet [5]. The wavelets extract voltage and current features and use a decision tree to identify the islanding.…”
Section: Introductionmentioning
confidence: 99%